2020
DOI: 10.1016/j.jaci.2020.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Endotypes of chronic rhinosinusitis: Impact on management

Abstract: Following the trend in asthma, endotypes for chronic rhinosinusitis with nasal polyps have been established, with type 2 immune reactions representing >80% of nasal polyp cases in Europe and the United States. Endotyping is without doubt useful to predict the natural course of disease, to determine pharmacotherapy and the extent of surgery, and lately also to select patients for treatment with type 2 biologics. However, with the opening of this new era of treatment, limitations of the current possibilities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 32 publications
0
74
0
2
Order By: Relevance
“…Some mAbs have recently been proved in phase 3 trials as efficient therapy on nasal polyp size and reduction of severity of symptoms [44]. Improving the understanding of different endotypes should provide insight for determining appropriate current and new therapies [45][46][47][48]. Kim et al concluded that endotypes depend on the epithelial barrier function, epithelial cytokines, and T cell subsets [46].…”
Section: Discussionmentioning
confidence: 99%
“…Some mAbs have recently been proved in phase 3 trials as efficient therapy on nasal polyp size and reduction of severity of symptoms [44]. Improving the understanding of different endotypes should provide insight for determining appropriate current and new therapies [45][46][47][48]. Kim et al concluded that endotypes depend on the epithelial barrier function, epithelial cytokines, and T cell subsets [46].…”
Section: Discussionmentioning
confidence: 99%
“…For the endotyping of CRS, the measurement of cytokines and chemokines is useful [9,37,38]. Emerging evidence has indicated that several biologics targeting Th2 cytokines as well as IgE show promise as therapeutics for severe and uncontrolled ECRS [39]. Thus, for appropriate, effective, and successful therapy, endotyping of CRS is important [9,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has indicated that several biologics targeting Th2 cytokines as well as IgE show promise as therapeutics for severe and uncontrolled ECRS [39]. Thus, for appropriate, effective, and successful therapy, endotyping of CRS is important [9,[38][39][40]. Recent reports using gene expression analysis and a genome-wide association study have revealed the significance of 15-LOX-1 in the pathogenesis of CRSwNP [20,21,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Рекомендуется проводить анализ эффективности терапии через 16 недель после старта. Самым чувствительным клиническим показателем является обоняние, улучшение которого может быть зарегистрировано уже на 4-8 неделе от начала использования биологической терапии [33]. Достижение улучшений по всем 5 критериям оценки будет свидетельствовать об отличном ответе, по 3-4 критериям среднем ответе, по 1-2 критериям плохом ответе и, соответственно, отсутствие изменений по всем критериям оценки будет свидетельствовать об отсутствии ответа.…”
Section: ;19;3(106)unclassified